2014
DOI: 10.1111/1467-8268.12084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV/AIDS and Microfinance of Women on Income, Medical Expenditures and Schooling in Côte d'Ivoire

Abstract: This paper examines the issue of HIV and AIDS in relation to women, human capital and microfinance in Côte d'Ivoire. In total, 440 women and two microfinance institutions (MFIs) served as study units. The HIV epidemic negatively affected both the human and financial capital of households. The morbidity of HIV/AIDS-affected respondents negatively influenced the level of their income. MFI credit failed to increase HIV-positive women's income, while they faced higher medical expenditures than non-affected women. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
2
0
1
Order By: Relevance
“…De nombreuses études ont examiné les effets d'une épidémie sur l'économie. La plupart ont porté sur le VIH (Adedeji & Akinlo, 2016; Anyanwu et al, 2013; D'Adda et al, 2009; Fofana et al, 2014; Glick et al, 2009; Haacker, 2002, 2004; Kasirye, 2016) et sur l'épidémie du SARS1 (Lee & Mckibbin, 2004; Wen et al, 2004; Mckibbin et al, 2006). La COVID‐19, plus contagieuse que le VIH et le SARS a touché la grande majorité des pays du globe de façon subite, et a suscité de leur part, des réponses appropriées afin d'endiguer la propagation de la pandémie.…”
Section: Revue De La Littératureunclassified
“…De nombreuses études ont examiné les effets d'une épidémie sur l'économie. La plupart ont porté sur le VIH (Adedeji & Akinlo, 2016; Anyanwu et al, 2013; D'Adda et al, 2009; Fofana et al, 2014; Glick et al, 2009; Haacker, 2002, 2004; Kasirye, 2016) et sur l'épidémie du SARS1 (Lee & Mckibbin, 2004; Wen et al, 2004; Mckibbin et al, 2006). La COVID‐19, plus contagieuse que le VIH et le SARS a touché la grande majorité des pays du globe de façon subite, et a suscité de leur part, des réponses appropriées afin d'endiguer la propagation de la pandémie.…”
Section: Revue De La Littératureunclassified
“…D’Adda et al (2009) explored the interaction between an ACC deaminase‐producing bacterial strain and an arbuscular mycorrhizal fungus and their effects on cucumber growth under salinity. Fofana et al (2014) studied the evolutionary characteristics and prognostic factors of tetanus at the Point G University Hospital in Bamako, Mali. Glick et al (2009) discussed plant growth promotion by bacterial ACC deaminase.…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical studies do not always show that microcredit has a positive effect on women's welfare and empowerment. First, several empirical studies found no effect from microcredit on household income as well as on women's empowerment (e.g., see Coleman, 1999; Crépon, Devoto, Duflo, & Parienté, 2015; Fofana, van Ophem, Niehof, & Antonides, 2014; Goetz & Gupta, 1996; Rahman, 1999). Recently Banerjee, Duflo, Glennerster, and Kinnan (2015) did not find significant differences in health, education, or women's empowerment between the control and treatment groups in a group‐lending microcredit programme in Hyderabad, India.…”
Section: Introductionmentioning
confidence: 99%